2008
DOI: 10.1258/td.2008.070359
|View full text |Cite
|
Sign up to set email alerts
|

A structured training module using an inexpensive endotrainer for improving the performance of trainee surgeons

Abstract: Training in minimal access surgery has always been difficult in developing countries with limited resources, non availability of formal animal labs, inaffordability of conventional endotrainers and lack of trained endosurgeons to help the amateurs. It is always difficult to start a new procedure in such places where not only the patients but the orthodox surgical fraternity are reluctant to accept new ideas and newer trends in surgery. After thorough discussions with senior surgeons, the author (who was the on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…In Mongolia, more than 315 Mongolian practitioners received laparoscopic training over 9 years (2005-2013), and laparoscopic cholecystectomy surpassed open cholecystectomy as the primary method for gallbladder removal at a national scale [32]. Lectures, workshops, laboratory-based trainers, makeshift trainer boxes, and animal models can be used to build skills outside of the operating room [34][35][36][37][38]. Competency based training with and pre-and post-test evaluations and a designated number of procedures should be required for graduation [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…In Mongolia, more than 315 Mongolian practitioners received laparoscopic training over 9 years (2005-2013), and laparoscopic cholecystectomy surpassed open cholecystectomy as the primary method for gallbladder removal at a national scale [32]. Lectures, workshops, laboratory-based trainers, makeshift trainer boxes, and animal models can be used to build skills outside of the operating room [34][35][36][37][38]. Competency based training with and pre-and post-test evaluations and a designated number of procedures should be required for graduation [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…53 Studies from Tanzania, India, and Botswana have demonstrated significantly better technical outcomes after laparoscopic simulation. [54][55][56] However, laparoscopic simulation has not been widely rolled out to teach laparoscopic CRS in LMICs. Low-fidelity, low-cost simulation can also be used to teach open CRS procedures.…”
Section: Surgical Simulation In Crs Trainingmentioning
confidence: 99%
“…Moreover, in many LMICs it is difficult to promote new ideas in surgery, not only among patients but also among local surgeons due to cultural and social barriers [ 5 ]. However, initiatives are being implemented in LMICs in order to train dedicated health workers and to promote laparoscopy, especially in order to minimize post-surgical infection and to reduce recovery time [ 6 , 7 ]. More importantly, the advantages of laparoscopy compared to open surgery could be even more evident in settings with limited access to blood transfusion, clean water, and poor healthy living conditions [ 8 ].…”
Section: Introductionmentioning
confidence: 99%